Effect of oral administration of probiotics on intestinal colonization with drug-resistant bacteria in preterm infants - Abdullah Kurt; Deniz Anuk Ince; Ayşe Ecevit; Özlem Kurt Azap; Zafer Ecevit; Ersin Öğüş; Ali Ulaş Tuğcu; Aylin Tarcan (Indonesian Pediatric Society, 2017)
Background Oral administration of probiotics in newborn preterm infants has been shown to be helpful, especially ın reducıng the incidence of necrotizing enterocolitis and overall mortality rates.Objective To evaluate the effect of probıotıc supplementation on ıntestınal colonization by antibiotic-resistant microorganisms in preterm infants receiving antibiotics in a neonatal intensive care unit (NICU).Methods The prospective, randomized trial was performed ın preterm infants who were hospitalized in the NICU at Baskent University Ankara Hospital between January 2011 and February 2012. A total of 51 infants were enrolled and randomly assigned to one of two groups: Group 1 (n=27) received probiotic therapy and Group 2 (n=24) did not receive probiotics. The probiotic used was Lactobacillus reuteri (Biogaia® AB, Sweden). Subjects underwent weekly nasal swab and stool cultures for a maxımum of 6 weeks, and at the tıme of dıscharge ıf thıs was prıor to 6 weeks. All posıtıve cultures were further tested for culture-specıfıc ıdentıfıcatıon and antıbıotıc suceptibility.Results A total of 607 cultures were evaluated. Posıtıve cultures were found ın 37.9% from Group 1 and 35.2% from Group 2. Intestınal colonızatıon by antıbıotıc-resıstant bacterıa dıd not sıgnıfıcantly dıffer between groups (P>0.05). Conclusions Oral supplementation with probiotics do not prevent the intestınal colonization of antibiotic-resistant microorganisms in preterm NICU patıents who receıved antıbıotıc treatment.